Structural, electrical, and acoustical properties of graphene oxide films for acoustoelectronic applications. Issue 8 (21st April 2017) - Kuznetsova, Iren; Kolesov, Vladimir; Zaitsev, Boris; Tkachev, Sergey; Kashin, Vadim; Shikhabudinov, Alexander; Fionov, Alexander; Gubin, Sergey; Sun, Shaorong
Abstract : Graphene oxide (GO) possesses some unique properties, which allow its technological applications in many fields (energy storage, microelectronic devices, and chemical sensors). It can also be used as a sensitive layer in the development of the chemical acoustoelectronic sensors. We characterized the produced GO films by measuring their structural properties, permittivity, and longitudinal/shear elastic moduli. For the first time, we determined the longitudinal and shear elastic moduli of a GO film under study to be 12.3 ± 0.1 MPa and 3.0 ± 0.1 MPa, respectively. The density of the GO film is equal to ∼850 kg m −3 . The permittivity of the GO film was found to be 21 for a frequency f  = 20 Hz. The obtained results may be used in further application of GO films in acoustoelectronic sensor devices.